Analisis Kesalahan Berbahasa dalam Teks Nonfiksi pada Buku Pelajaran Bahasa Indonesia Kelas VIII Terbitan Pusat Kurikulum dan Perbukuan Balitbang Kementerian Pendidikan dan Kebudayaan sebagai Upaya Meningkatkan Kualitas Pembelajaran Membaca - Rafanida Alyafatin; Izatul Atiya Pasah; Nia Mila Dina Setiani; Hening Jati Melani; Anggun Rizka Ramadania; Asep Purwo Yudi Utomo; Aang Fahruddin Dwi Hatmanto (Universitas Palan, 2024)
The use of the Indonesian language, particularly in spelling, has not been fully executed properly, especially in textbooks. Textbooks, especially Indonesian language textbooks, as the primary learning source, should serve as examples of standardized and error-free texts. However, in reality, many language errors are still found in the non-fiction texts of Indonesian language textbooks. This research describes syntax language errors in the Indonesian Language Textbook for Grade VIII published by the Curriculum and Book Development Center of the Ministry of Education and Culture. The research method used is Qualitative Descriptive. The results of the research include language errors in the Grade VIII Indonesian Language Textbook published by the Curriculum and Book Development Center of the Ministry of Education and Culture in the field of syntax, which include: conjunction errors, punctuation errors, misspellings not in accordance with KBBI (Indonesian Dictionary), and sentence ineffectiveness. From the research findings, it can be concluded that Indonesian language textbooks serve as good learning resources, but the various errors found indicate that Indonesian language textbooks are still not effective for learning. This research was conducted to identify language errors in Indonesian language textbooks in order to pay more attention to their effectiveness in learning.